2018
DOI: 10.1002/mc.22784
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation‐associated urothelial cytochrome P450 oxidoreductase predicates the xenobiotic‐metabolizing activity of “luminal” muscle‐invasive bladder cancers

Abstract: Extra‐hepatic metabolism of xenobiotics by epithelial tissues has evolved as a self‐defence mechanism but has potential to contribute to the local activation of carcinogens. Bladder epithelium (urothelium) is bathed in excreted urinary toxicants and pro‐carcinogens. This study reveals how differentiation affects cytochrome P450 (CYP) activity and the role of NADPH:P450 oxidoreductase (POR). CYP1A1 and CYP1B1 transcripts were inducible in normal human urothelial (NHU) cells maintained in both undifferentiated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
5
6
0
Order By: Relevance
“…Two bands were detected on the Western blot for CYP1A1; the top band is the correct molecular weight (58 kDa), and thus, the lower band is assumed to be nonspecific. This is consistent with other studies using this antibody to detect human CYP1A1 in other cultured BaP-treated human cells (Hamouchene et al, 2011; Wohak et al, 2016; Baker et al, 2018). Previous investigations in our laboratory have shown that the top band increases with higher BaP concentrations used and also that only the top band is diminished when BaP-treated cells have been transfected with CYP1A1 siRNA (Kucab & Arlt, unpublished data).…”
Section: Resultssupporting
confidence: 92%
“…Two bands were detected on the Western blot for CYP1A1; the top band is the correct molecular weight (58 kDa), and thus, the lower band is assumed to be nonspecific. This is consistent with other studies using this antibody to detect human CYP1A1 in other cultured BaP-treated human cells (Hamouchene et al, 2011; Wohak et al, 2016; Baker et al, 2018). Previous investigations in our laboratory have shown that the top band increases with higher BaP concentrations used and also that only the top band is diminished when BaP-treated cells have been transfected with CYP1A1 siRNA (Kucab & Arlt, unpublished data).…”
Section: Resultssupporting
confidence: 92%
“…CYP1A1 and CYP1B1 activities, but not CYP1A2 activity, were detected in RT4 cells. These data are in agreement with previous reports on CYP1A1 and CYP1B1 protein (Plottner et al 2016), and enzyme activity (Baker et al 2018;Reshetnikova et al 2016) in RT4 cells. The complete inhibition of CYP1A1 and CYP1B1 by α-NF resulted in a 50% decrease in the levels of AαC DNA adducts in RT4 cells, signifying that these isoforms prominently carry out the bioactivation of AαC in RT4 cells.…”
Section: Discussionsupporting
confidence: 94%
“…Subtype-related pathways presented in this study ( Tables 1 , 2 ) are largely consistent with the previously identified ( Choi et al, 2014a ; Hurst and Knowles, 2014 ; McConkey et al, 2016 ; Ochoa et al, 2016 ; Hau et al, 2017 ; Seiler et al, 2017 ; Baker et al, 2018 ). In general, pathways that are involved in the EMT, metastasis, and immune system process, are upregulated in the basal subtype, whereas, metabolic-related pathways are upregulated in the luminal subtype.…”
Section: Discussionsupporting
confidence: 91%